Frequency of hypodontia in patients aged 7 to 15 years through a radiological study - Naccha Torres, Andrés (2022)
Objective: To determine the frequency of hypodontia found by panoramic radiographs in patients between 7 and 15 years of age who attended the Institute of Maxillofacial Diagnosis (IDM) in the period between 2016 and 2020. Materials and methods: The study was observational, cross-sectional, retrospective and descriptive. Four hundred panoramic radiographs were used to detect the absence of teeth, type of teeth, number of affected teeth, maxilla, age and sex through structured observation. Results: The frequency of hypodontia found by panoramic radiographs in patients between 7 and 15 years old who attended the Institute of Maxillofacial Diagnosis (IDM) between 2016 and 2020 was 8.5%, the second premolar presented the highest frequency of hypodontia with 58.8%. According to the number of pieces, a percentage of 44.1% was found in patients with an affected piece; the highest frequency of hypodontia occurred in the lower jaw with 57.38%; patients between 13 and 15 years of age presented the highest frequency of hypodontia with 52.9% and the frequency of hypodontia was higher in women with 55.9%. Conclusions: The frequency of hypodontia in panoramic radiographs in patients between 7 and 15 years of age who attended the Institute for Maxillofacial Diagnosis (IDM) between 2016 and 2020 was 8.5%; The highest frequency of hypodontia was presented by the second premolar, in a single piece, in the lower jaw, in patients between 13 and 15 years of age, as well as in the female sex.